On Implementing Usability Evaluation Activities within Agile Environment: A Plan Based-Process - Salman, Fouad Abdulameer; Deraman, Aziz; Abdul Jalil, Masita; Fahmy, Syahrul (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In fast-paced software development cycles, poor governance may cause a loss of focus on the overarching objectives and implementation of usability work. We propose a conceptual framework that would assist software development teams in understanding and implementing usability evaluations in the described agile environments. The framework provides a common language that conveys the “big picture” of software development, details the roles needed for usability, and facilitates the analysis, discussion and communication of responsibilities and decision structures. The framework is supported by a visual mapping guideline that eases discussion and simplifies the process of incorporating usability work in companies.